Development of Android-Based Package Sorting Application Based on Distance - Arya, Dionisius; Romli, Ali (P3M Politeknik Negeri Bengkalis, 2024)
In the operational logistics of goods delivery, the effectiveness of couriers in organizing and managing packages plays a crucial role in optimizing delivery routes. The objective of developing this Android-based package sorting application is to reduce errors in the sorting process before packages are placed into storage bags. With the help of this application, couriers can prioritize the farthest packages for loading into the storage bags first, while stacking the nearest packages on top. The methodology employed involves scanning package receipts using barcodes and calculating distances based on the coordinates of the courier and the recipient using the Haversine formula. The application was tested using black-box techniques, ensuring that each feature functions as expected. Additionally, testing was conducted with five couriers and five admin staff from the delivery company by providing a questionnaire containing questions about the developed application. The number of errors before and after using the application was used to determine the success of error reduction in the package sorting process. The results from the questionnaire indicate a 96.88% reduction in sorting errors, signifying that the developed application effectively lowered the error rate during the package sorting process. This reduction in errors leads to a faster sorting process, providing benefits such as decreasing delivery delays, which significantly enhances customer satisfaction and improves the quality of the delivery company.